Analysis of the account of slot harmonics in stator’s EMF in mathematical modeling of the process of testing induction motors by the mutual load method - V. V. Kharlamov; D. I. Popov (Омский научный вестник)
The article presents the results of mathematical modeling of induction motors powered by frequency converters taking into account slot harmonics of EMF and stator current due to corresponding pulsation of magnetic field induction in air gap. The results of calculations for low, medium and high-power engines are presented. It is shown that the spectrum-current analysis method can be used to determine rotation speed of induction machines when they are tested by the mutual load method using various schemes. The method for determining the intervals for searching for slot harmonics is proposed.